Adverse childhood experiences, mental health, and quality of life of Chilean girls placed in foster care : an exploratory study - Seiler, Annina; Kohler, Stefanie; Ruf-Leuschner, Martina; Landolt, Markus A. (My University, 2016)
In Latin America, little research has been conducted regarding exposure to adverse childhood experiences (ACEs), mental health, and health-related quality of life (HRQoL) among foster children. This study examined the association between ACEs and mental health, posttraumatic stress disorder (PTSD), and HRQoL in Chilean foster girls relative to age-matched Chilean family girls. Data were obtained from 27 Chilean foster girls and 27 Chilean girls ages 6 to 17 years living in family homes. Standardized self- and proxy-report measures were used. Foster girls reported more ACEs than controls in terms of familial and nonfamilial sexual abuse and both emotional and physical neglect. Girls living in foster care had a significantly higher rate of PTSD, displayed greater behavioral and emotional problems, and reported a lower HRQoL. Analysis confirmed the well-known cumulative risk hypothesis by demonstrating a significant positive association between the number of ACEs and PTSD symptom severity and a significant negative association with HRQoL. Chilean foster girls endured more ACEs that impair mental health and HRQoL than age-matched peers living with their families. These findings have implications for out-of-home care services in Latin America, highlighting the need to implement not only appropriate trauma-focused treatments but also appropriate prevention strategies. (PsycINFO Database Record
Keywords: 150